Fathers’ Involvement in Child Health Care: Associations with Prenatal Involvement, Parents’ Beliefs, and Maternal Gatekeeping - Zvara, B.J. (Fam Relat, 2013)
Using data from 182 dual-earner couples experiencing the transition to parenthood, this study examined associations between prenatal involvement, gender role beliefs, and maternal gatekeeping and new fathers’ involvement in child health care. Results indicated that prenatal father involvement was associated with both fathers’ direct engagement in child health care and fathers’ perceived influence in child health-related decision-making. Fathers also demonstrated greater direct engagement in child health care when mothers held more nontraditional beliefs about gender roles. Moreover, when mothers were more encouraging of fathers’ involvement in childrearing, fathers felt more influential in child health-related decision-making, whereas when mothers engaged in greater gate closing behavior, fathers with more traditional gender role beliefs felt less influential in child health-related decision-making. This study suggests that fathers’ prenatal involvement, mothers’ beliefs, and maternal gatekeeping may play a role in the development of new fathers’ involvement in child health care at the transition to parenthood.